PEMADATAN TANAH DAN INFILTRASI DI KAWASAN WISATA BATURADEN, PURWOKERTO - , ANDA BRAHMANTYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Natural tourism is an alternative non-timber forest management that is relatively friendly to the environment. The activity has positive impact in economic growth, but also has negative impact, such as soil compaction. This research studies about soil compaction and infiltration in Baturaden Tourist Area which administratively located in Purwokerto, Banyumas Regency, Central Java Province with total area 16,5 Ha. Attraction area that are being used as research site are Natural Forest, Camping Ground, Pancuran Telu, Pancuran Pitu, and Telaga Sunyi. The objective of this research is to measure the value of BV, BJ, porosity, and infiltration on each research sites